Discrete-time sliding mode control based on exponential reaching law of a pneumatic artificial muscle actuator / Quy-Thinh Dao and Trung-Kien Le Tri - Dao, Quy-Thinh; Tri, Trung-Kien Le (Universiti Teknologi MARA, 2022)
In this paper, a discrete-time sliding mode control (DSMC) approach based on exponential reaching law (ERL) is developed for a pneumatic artificial muscle (PAM) system to achieve high tracking performance and chattering alleviation. The proposed controller is designed based on an exponential term that dynamically adapts to the variation of the switching function, thus guarantees finite steps convergence and chattering phenomenon reduction simultaneously. Moreover, the effectiveness of the designed controller and its stability on a dual actuator PAM-driven system is demonstrated under various conditions. In addition, a leg-gait pattern is set as trajectory tracking for further validation. Finally, experiment results show that the proposed approach is effective and promising for rehabilitation applications.